Review—Prospects of Nanomaterial-Based Biosensors: A Smart Approach for Bisphenol-A Detection in Dental Sealants. Issue 2 (1st February 2022) - Verma, Damini; Yadav, Amit K.; Rathee, Garima; Dhingra, Kunaal; Das Mukherjee, Maumita; Solanki, Pratima R.
Abstract : The use of Bisphenol-A (BPA) and its derivatives are rapidly increasing in dentistry for dental sealants and composite filling materials. The release of BPA from polymerized resin into saliva has aroused considerable concern regarding exposure to xenoestrogen by dental treatment. Many shreds of evidence have stated that leakage of BPA and its derivatives has posed health risks problems due to its endocrine-disrupting estrogenic properties. Various conventional techniques were designed for estimating leached BPA from dental sealants but having lengthy, complex procedures and requirements of technical experts, rapid utilization of these techniques is difficult. However, biosensors have emerged as a strong alternative to overcome these limitations. A vast range of electrochemical biosensors based on carbon and metal nanomaterials, molecularly-imprinted polymers, quantum dots, metal-organic frameworks, and polymer nanocomposites have been introduced for screening of BPA in real samples. But no study has been done to test leached BPA from dental sealants using biosensors. Therefore, we have provided an outlook of nanomaterials-based biosensors to test leached BPA from dental sealants. The present review also highlights different studies that assessed the absence/presence of BPA in the oral cavity after its use in dental materials. It also describes the challenges and future prospects in the progress of BPA-based biosensors.